1996
DOI: 10.1183/09031936.96.09071500
|View full text |Cite
|
Sign up to set email alerts
|

Protected bronchoalveolar lavage in the diagnosis of ventilator-associated pneumonia

Abstract: The sensitivity of protected bronchoalveolar lavage quantitative cultures was 87% and the specificity 91%. The sensitivity of cytological analysis for intracellular organisms was 75% and the specificity 98%. According to our results, if the patient is already on antibiotics, the direct examination of protected bronchoalveolar lavage fluid is less reliable, although still helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…A final result of 10 3 cfu/ml would indicate that the original material sampled in the airway contained a concentration of bacteria of 10 6 cfu/ml. Many studies have verified these findings and have found that bronchoalveolar lavage (BAL) provides similar information although with a cut-off value of 10 4 cfu/ml or more [26,27,28,29]. Studies that have failed to support the findings of Chastre et al [25] generally suffer from one or more critical faults, the most important of which is failure to account for antibiotic therapy appropriately.…”
Section: Diagnosis Of Nosocomial Pneumoniamentioning
confidence: 75%
“…A final result of 10 3 cfu/ml would indicate that the original material sampled in the airway contained a concentration of bacteria of 10 6 cfu/ml. Many studies have verified these findings and have found that bronchoalveolar lavage (BAL) provides similar information although with a cut-off value of 10 4 cfu/ml or more [26,27,28,29]. Studies that have failed to support the findings of Chastre et al [25] generally suffer from one or more critical faults, the most important of which is failure to account for antibiotic therapy appropriately.…”
Section: Diagnosis Of Nosocomial Pneumoniamentioning
confidence: 75%
“…Note that there is a considerable overlap in clinical definitions in terms of fever, leukocytosis, purulent sputum, and change in oxygenation. 22 Some clinicians and investigators have relied on a combination of these factors that are included in the clinical pulmonary infection score (CPIS). [23][24][25][26] A score of at least 6 has been suggested as a marker of VAP.…”
Section: Diagnosis and Definitionsmentioning
confidence: 99%
“…Bronchoalveolar lavage cultures have been advocated as a good technique to diagnose pneumonia in critically ill patients, with a sensitivity and specificity as high as 87% and 91%, respectively. [7][8][9] However, in a recent review, Ramzy et al 10 showed a lack of correlation of positive BAL culture results with abnormal radiographic chest examination results in burn patients.…”
Section: Commentmentioning
confidence: 99%